An investigation of Nitrospira bacteria in coastal wetlands of China: distribution pattern and related environmental driving factors - Zhao, Qiang; Sun, Dongyao; Tang, Xiufeng; Hou, Lijun; Liu, Min; Han, Ping (Frontiers in Marine Science, 2023)
Nitrate is mainly converted via aerobic nitrite oxidation during the second step of nitrification, which is catalyzed by nitrite-oxidizing bacteria (NOB) and the recently discovery complete ammonia oxidizers (comammox). Members of the genus Nitrospira are the most diverse and widespread known NOB and comammox. However, the community assembly of Nitrospira in estuary and coastal wetland and the major environmental shaping factors remain understudied. Here in this study, we investigated the geographical distribution pattern of Nitrospira along the large-scale coastal wetlands of China. The results showed that the abundance of Nitrospira ranged from 4.96×106 - 3.88×107 copies/g dry sediment, significantly (more than one order of magnitude) higher than amoA gene of ammonia-oxidizers. The identified Nitrospira belong to Nitrospira lineage IV (50%), lineage I and II. The adaptability of the three lineages to environmental factors (such as temperature, pH, salinity and particle size) are different, which leads to the diversity of its distribution composition in different estuaries. Network analysis showed that the cooperation takes greater portion than competition in the relationship of Nitrospira population. This study revealed the abundance and community composition of Nitrospira bacteria, as well as the major environmental driving factors in coastal wetland ecosystems, which deepens our understanding of the niche separation of Nitrospira with the nitrogen cycling.